A QUALITATIVE RESEARCH ON THE EFFECTS OF SCHOOLS IN ARCHITECTURE - İnnab, Nagihan; YILMAZ, Niyazi (Atlas Journal, 2023)
The relationship of the individual with the place is among the main determinants of his attitudes and behaviors. Along with these determinants, the effect of space on the individual is an undeniable point in terms of spirituality. From both a spiritual and behavioral point of view, the biggest factor that directs human life is the effect of the place on itself. In the light of this information, schools, which appear as a spatial dimension in an education context, have an important place within the scope of the individual-space relationship since they cover an important period of the individual's life. Especially primary and secondary education schools are education-based spatial designs that most affect the childhood and youth period of the individual. Schools are not just for students; It is also an important spatial determinant for teachers, school administrators and other servants. The existing architecture of the schools largely shapes the sense of responsibility, crisis management, anxiety, awareness, academic success, professional competence and most importantly, the sense of belonging for the individuals who spend a certain period of their lives here. In this research, the data obtained from a secondary education institution in Istanbul Province were analyzed qualitatively. The phenomenological model was used with a metaphorical approach and the findings were interpreted. In the study, data were collected with a semi-structured interview form. The research group consists of 112 participants in total, consisting of teachers, students and school administrators. It is aimed to determine what the spiritual effects of school architecture on the participants are metaphorically.